Coastal and estuarine risk assessment (Lewis Publishers, 2002)
Risk assessment is the cornerstone of contemporary environmental protection. You must find the answers to questions such as: what might be the impacts of the new synthetic chemicals, what problems might arise from the normal operations of industry, what are the chances of accidental releases and how will they impact the environment? Understanding and assessing these risks is essential to sound environmental policy and management.The first book to address the application of the current National Research Council (NRC) risk assessment paradigm to the coastal marine environment, Coastal and Estuarine Risk Assessment covers topics that range from pollutants of emerging concern to bioavailability and bioaccumulation at the suborganismal through landscape levels. It explores the necessary applications for modifying the NRC paradigm and presents a series of steps to actually accomplish an effective assessment using the modified paradigm. The book highlights the logical framework for assessing causation, and measurement of toxicant fate and effect. The chapter authors bring together experiences from academia, private consultants, and government agencies, resulting in a rich mixture of experience and insights. Exploring the science of exposure, effect, and risk in coastal and estuarine environments, Coastal and Estuarine Risk Assessment gives you a building block approach to the fundamental components of risk assessment.